(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the outcomes of surgical repair of zone I extensor tendon injuries of the fingers at 108 Military Central Hospital. Materials and Methods: A cross-sectional descriptive study was conducted on 69 patients who underwent primary repair of zone I extensor tendon injuries at the Department of Upper Limb and Microsurgery, 108 Military Central Hospital, from January 2020 to June 2025. Surgical outcomes were assessed after 6 months using the Miller scoring system. Results: Male patients accounted for 78.3%, mean age 40.6 years. Sports injuries were most common (50.7%). The little finger was most frequently affected (58.0%). No infections were observed. Re-rupture occurred in 10.4%. Good and fair outcomes accounted for 73.9%. Conclusion: Primary repair provides favorable outcomes and is an effective treatment option.